The Effectiveness of Character Education Based Blended Learning Model to Improve Children Critical Thinking Skills In Islamic Religious Education - Wantu, Hasyim Mahmud; Arif, Muh.; Tola, Baso; Damopolii, Mujahid; Kaawoan, Selvi Yanti (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of a character education-based blended learning model to improve Children' critical thinking skills in Islamic religious education. This research is quantitative research with a meta-analysis approach. The criteria for study eligibility are research obtained through google scholar; Researchgate, ERIC, ScienceDirect and Emerald; research comes from Sinta and Scopus indexed journals or proceedings; Research should be relevant to the effectiveness of character education-based blended learning models to improve Children' critical thinking skills in Islamic religious education; The study was published in 2020-2024 and reported complete values to calculate the value of effect size. Statistical analysis with JASP 0.8.5 application. The results concluded a) the study concluded 20 studies with normal and heterogeneous distribution; b) there is a significant influence of the character education-based blended learning model to improve Children' critical thinking skills in Islamic religious education with strong categories (rE = 0.851; p < 0.001), and c) there is no publication bias. This finding explains that the blended learning model based on the character education-based blended learning model is effective for improving Children' critical thinking skills in Islamic religious education.Â